Wygnani z raju - analiza toposu domu w filmach Andrieja Zwiagincewa - Tes, Urszula (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The topos of ‘home’ is one of the most important motifs in Andrey Zvyagintsev’s films. The director perceives ‘home’ as a material and symbolic term. It applies to the place where a family lives and to the house of God. The article refers to Eliade’s well-known concept of home, but also to the more modern one created by Zbigniew Kadłubek, who writes about oikology in the context of faith. The article reveals the richness of mythical, cultural, religious and artistic references. Each film exposes different images of ‘home’, but they use common metaphors, such as the fall, destruction and the apocalypse. Contemporary man, turned away from God, recreates the mythical thread of exile and ceases to have a safe place to be in the world. In such works as The Banishment, Leviathan, Elena, and Loveless, the director fully showed the consequences of losing the spiritual dimension of life. The proposed interpretations of Zvyagintsev’s films expand the reception of his work in Poland.